PHENOMENA, NOUMENA, AND “TRIGGERS” OF MUSICAL STYLE FORMATION - Katrych, Olha (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study is explained both by the lack of conceptual studies in contemporary musicology devoted to the dramaturgy of style formation and by the fundamental role of style-related issues in musical art. The study focuses on the processes of musical style formation. A spectrum of interactions between musical and extra-musical factors that determine the shaping of style in music is examined. The ontological foundations of sound–intonation production of stylistic phenomena are conceptualized, and the genealogy of sociocultural mechanisms inspiring stylistic processes is traced. The analytical lens of the research is musical communication, which encompasses the continuity of the “creation — reproduction — perception” chain in music and takes into account the socio-historical context of stylistic formation. Main objectives of the study is to deepen the understanding of the ontology and genesis of the system of musical style formation. The methodology combines the concepts of V. Moskalenko’s theory of musical creativity style and the author’s own conception of performing-musician style. The research applies a complex methodology integrating historical–dialectical and musicological approaches, discourse analysis, theoretical generalization, comparative musicology, as well as methods of analysis and synthesis. The main results and conclusions interpret style formation as a systemic phenomenon of procedural nature, whose concentric structure is conditioned by the interrelation of stylistic levels (epochal style, historical-period style, school style, national style, individual style, and the style of a particular work) and the continuity of musical-communicative mechanisms of creation, reproduction, and perception. In light of current music-interpretative discourse, perspectives for the future dynamics of musical style formation are outlined.